Product applications and technology directions with SiGe BiCMOS. - Joseph, A.J (IEEE Journal of solid state circuits)
In this paper, we highlight the effectiveness and flexibility of SiGe BiCMOS as a technology platform over a wide range of performance and applications. The bandgap-engineered SiGe heterojunction bipolar transistors (HBTs) continue to be the workhorse of the technology, while the CMOS offering is fully foundry compatible for maximizing IP sharing. Process customization is done to provide high-quality passives, which greatly enables fully integrated single-chip solutions. Product examples include 40-Gb/s (OC768) components using high-speed SiGe HBTs, power amplifiers compatible for cellular applications, integrated voltage-controlled oscillators, and very high-level mixed-signal integration. It is argued that such key enablements along with the lower cost and higher yields attainable by SiGe BiCMOS technologies will provide competitive solutions for the communication marketplace.